Preparation method and application of morphology-compounded iron phosphate

Iron phosphate was prepared by morphological complexing, combining the composite of sheet-like and block-like morphology, and solving the problem of difficult to take into account both high compaction density and discharge capacity in the prior art, achieving high efficiency and low energy consumption lithium iron phosphate preparation.

CN119409151APending Publication Date: 2025-02-11WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411754659.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art requires multiple mixed sintering when preparing high-pressure density lithium iron phosphate, which increases energy consumption and is difficult to take into account both high-pressure density and discharge capacity.

Method used

The morphological complex method is used to prepare iron phosphate, and the sheet-like morphology is generated through the first-stage oxidation reaction, and then the mass-like morphology is generated by the addition of maleic anhydride and the second-stage oxidation reaction, so as to achieve the complexity of sheet-like and mass-like morphology. , avoiding grading of large and small particles.

Benefits of technology

It is realized that lithium iron phosphate with high compaction density and large discharge capacity is obtained without performing large and small particle grading, reducing production energy consumption and improving the energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409151A_ABST
    Figure CN119409151A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of morphology-compounded iron phosphate. The preparation method comprises the following steps: S1, dissolving an iron source in a phosphoric acid solution to obtain a ferrous dihydrogen phosphate solution; s2, heating and stirring, adding a part of hydrogen peroxide, and carrying out a first-stage oxidation reaction to obtain a turbid liquid; s3, adding maleic anhydride into the obtained turbid liquid, fully mixing and stirring, adding the rest of hydrogen peroxide, carrying out two-stage oxidation reaction, and aging; s4, after the solvent is filtered out, washing, drying and roasting are conducted, and iron phosphate is obtained. The iron phosphate prepared by the method disclosed by the invention has two completely different morphologies, i.e., a sheet shape and a block shape, and the particle sizes of the sheet shape and the block shape are equivalent, so that the lithium iron phosphate does not need to be prepared through large and small particle grading, and meanwhile, the obtained lithium iron phosphate has the advantages of high compaction density and large discharge capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a morphology-compounded iron phosphate, and in particular to a preparation method and application of the morphology-compounded iron phosphate. Background Art

[0002] Lithium iron phosphate (LiFePO 4 , LFP) has attracted much attention as a positive electrode material for lithium-ion batteries. It has superior electrochemical properties and good kinetic characteristics, and can effectively carry out lithium intercalation and deintercalation processes, ensuring that the battery has stable charge and discharge performance and long cycle life. In addition, lithium iron phosphate does not contain rare or toxic metals, is environmentally friendly, has relatively low cost, and is relatively safe, and is considered to be the first choice for lithium-ion battery positive electrode materials.

[0003] Iron phosphate (FePO 4 As the main precursor of lithium iron phosphate, its morphology, specific surface area, iron-phosphorus ratio, particle size, etc. have an important influence on lithium iron phosphate. Among them, the morphology also has a direct impact on physical properties such as specific surface area and particle size, and further affects the charge and discharge capacity and compaction density of lithium iron phosphate. In addition, the compaction density of lithium iron phosphate material directly affects the energy density, charge and discharge rate and cycle life of the battery. A higher compaction density means that more active materials can be loaded into the battery cell, thereby improving the capacity and performance of the battery. At present, the industry mainly improves the compaction density of lithium iron phosphate by means of different particle size grading. For example, patent CN118373398B prepares lithium iron phosphate with different particle sizes by two sinterings, and then mixes them and sinters them for the third time to obtain high-density lithium iron phosphate; patent CN115806283A forms a staggered gradation of large and small grains by two sinterings; patents CN117303340A and CN 118561257 A obtain high-density lithium iron phosphate by premixing two kinds of iron phosphate to form a large and small particle gradation. However, the above methods require multiple mixing and sintering during the production process, which increases energy consumption and is not conducive to automated production. Patents CN118515253A and CN118324108A achieve high-density lithium iron phosphate by directly preparing composite iron phosphate. However, the above patents still achieve high compaction by grading the size of lithium iron phosphate particles, and the excessive size of lithium iron phosphate particles will hinder lithium ion transmission and is not conducive to capacity utilization.

[0004] Therefore, developing a method to achieve high-density lithium iron phosphate without the need for large and small particle grading can not only reduce energy consumption, but also help to realize the full capacity of lithium iron phosphate under high compaction. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a preparation method and application of morphologically composited iron phosphate. The iron phosphate prepared by the method of the present invention has two completely different morphologies, flaky and blocky, and the particle sizes of the flaky and blocky microscopic morphologies are comparable, so there is no need to prepare lithium iron phosphate by grading large and small particles. At the same time, the obtained lithium iron phosphate has the advantages of high compaction density and large discharge capacity.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing morphology-compounded iron phosphate comprises the following steps:

[0008] S1, dissolving an iron source in a phosphoric acid solution to obtain a ferrous dihydrogen phosphate solution;

[0009] S2, heating and stirring, adding a portion of hydrogen peroxide, performing a first-stage oxidation reaction, and obtaining a suspension;

[0010] S3, adding maleic anhydride to the obtained suspension, mixing and stirring thoroughly, adding the remaining hydrogen peroxide, carrying out a two-stage oxidation reaction, and aging;

[0011] S4, filtering off the solvent, washing, drying, and then roasting to obtain ferric phosphate.

[0012] In some examples of the present invention, in step S1, the iron source is one or more of reduced iron powder, iron block, iron sheet, ferroferric oxide, and ferrous oxide with a molar purity of metallic Fe>99%;

[0013] Preferably, the usage ratio of the iron source and the phosphoric acid solution in step S1 is 1:(2-3.5) in terms of the molar ratio of metallic Fe to phosphoric acid;

[0014] Preferably, the mass concentration of the phosphoric acid solution is 15-40%.

[0015] In some examples of the present invention, in step S2, the heating temperature is 45-95°C, preferably 65-85°C, and the stirring speed is 100-500 rpm.

[0016] In some examples of the present invention, the total amount of hydrogen peroxide added is 0.5-0.75 times the molar amount of metal Fe in the iron source;

[0017] Preferably, the amount of hydrogen peroxide added in step S2 is 20-80% of its theoretical total amount;

[0018] Preferably, the mass concentration of the hydrogen peroxide is 20-35%.

[0019] In some examples of the present invention, in step S2, the first stage oxidation reaction time is 10-50 minutes.

[0020] In some examples of the present invention, the maleic anhydride is added to the solution obtained in step S2 at a mass fraction of 0.01-10%, preferably 0.5-5%;

[0021] Preferably, after adding maleic anhydride, the reaction temperature is controlled to be 45-95° C., preferably 65-85° C., the stirring speed is 100-500 rpm, and the mixture is stirred for 20-60 minutes for thorough mixing before adding the remaining hydrogen peroxide.

[0022] In some examples of the present invention, in step S3, the second-stage oxidation reaction time is 10-70 minutes, and after the reaction, the aging reaction is continued at 70-95° C. for 60-120 minutes.

[0023] In some examples of the present invention, the calcination conditions in step S4 are: calcination at 500-650° C. for 3-6 hours.

[0024] The present invention also provides a morphologically composite iron phosphate prepared according to the method described above, which is characterized by having two composite morphologies, flaky and blocky. Preferably, the particle sizes of the flaky and blocky microscopic morphologies are comparable.

[0025] The present invention also provides an application of the morphology-compounded iron phosphate obtained by the method described above in the preparation of high compaction density lithium iron phosphate. The obtained lithium iron phosphate is widely used in lithium battery positive electrode materials.

[0026] The present invention firstly generates flakes through primary growth, then adds maleic anhydride to increase potential energy and change the morphology, and generates blocks through secondary growth. Thus, iron phosphate having both block and flake composite morphologies can be prepared. High compaction density of lithium iron phosphate can be achieved without grading of large and small particles, and at the same time, the discharge capacity is large, thus solving the problem of the difficulty in taking both compaction density and discharge capacity into consideration in existing products. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an electron microscope morphology of the iron phosphate prepared in Example 1.

[0028] Figure 2 This is the particle size distribution diagram of the iron phosphate prepared in Example 1.

[0029] Figure 3 This is an electron microscope morphology image of the iron phosphate prepared in Comparative Example 1.

[0030] Figure 4 This is an electron microscope morphology image of the iron phosphate prepared in Comparative Example 2.

[0031] Figure 5 This is an electron microscope morphology image of the lithium iron phosphate prepared in Application Example 1.

[0032] Figure 6This is an electron microscope morphology image of the lithium iron phosphate prepared in Application Example 4. DETAILED DESCRIPTION

[0033] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0034] "Range" disclosed herein is in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a particular parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range 3, 4 and 5 are listed, the following ranges can all be expected: 1-2, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0035] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations.

[0036] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0037] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0038] The preferred implementation methods of the present invention will be described in detail below in conjunction with specific embodiments. However, it should be understood that those skilled in the art can make reasonable changes, improvements and combinations to these embodiments without departing from the scope defined in the claims, so as to obtain new specific implementation methods. These new specific implementation methods obtained by changes, improvements and combinations are also included in the protection scope of the present invention.

[0039] [Example 1]

[0040] Prepare iron phosphate according to the following method:

[0041] S1. Dissolve 500 g of reduced iron powder in 35% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw material is added in a molar ratio of metallic Fe to phosphoric acid of 1:3;

[0042] S2, heating the solution to 70°C, adjusting the stirring speed to 300 rpm, adding 303.6 g of 27.5% hydrogen peroxide, carrying out a first-stage oxidation reaction, and reacting for 15 min to obtain a suspension;

[0043] S3, add maleic anhydride to the suspension at a mass fraction of 3.5%, stir at 80°C and 300 rpm for 30 min, add 303.6 g of 27.5% hydrogen peroxide after sufficient mixing, carry out a first-stage oxidation reaction, react for 15 min, adjust the temperature to 85°C and age for 120 min;

[0044] S4, after filtering off the solvent, washing, drying, and roasting at 550°C for 3h to obtain iron phosphate.

[0045] The electron microscope microscopic morphology of the iron phosphate prepared in this example is as follows Figure 1 As shown in FIG. 1 , it can be seen that the product is a composite morphology of flakes and blocks. In addition, the particle size distribution of the iron phosphate prepared in this embodiment is shown in FIG. Figure 2 As shown, it can be seen that the particle size distribution of the obtained iron phosphate is unimodal, and the particle sizes of the two iron phosphates with different morphologies are basically the same.

[0046] [Example 2]

[0047] Prepare iron phosphate according to the following method:

[0048] S1. Dissolve 500 g of reduced iron powder in 15% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw material is added in a molar ratio of metallic Fe to phosphoric acid of 1:3.5;

[0049] S2, heating the solution to 45°C, adjusting the stirring speed to 500 rpm, adding 441.6 g of 35% hydrogen peroxide, carrying out a first-stage oxidation reaction, and reacting for 40 min to obtain a suspension;

[0050] S3, add maleic anhydride to the suspension at a mass fraction of 5%, stir at 60°C and 400 rpm for 60 min, add 165.6 g of 35% hydrogen peroxide after sufficient mixing, carry out a first-stage oxidation reaction, react for 30 min, adjust the temperature to 75°C and age for 60 min;

[0051] S4, after filtering out the solvent, washing, drying, and calcining at 600°C for 4h to obtain flaky and block-shaped composite iron phosphate.

[0052] [Example 3]

[0053] Prepare iron phosphate according to the following method:

[0054] S1. Dissolve 500 g of reduced iron powder in 40% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw material is added in a molar ratio of metallic Fe to phosphoric acid of 1:2;

[0055] S2, heating the solution to 95°C, adjusting the stirring speed to 200 rpm, adding 200.6 g of 20% hydrogen peroxide, carrying out a first-stage oxidation reaction, and reacting for 50 min to obtain a suspension;

[0056] S3, add maleic anhydride to the suspension at a mass fraction of 0.5%, stir at 95°C and 500 rpm for 20 min, add 627.4 g of 20% hydrogen peroxide after sufficient mixing, carry out a first-stage oxidation reaction, react for 70 min, adjust the temperature to 90°C and age for 90 min;

[0057] S4, after filtering out the solvent, washing, drying, and calcining at 650°C for 5h, to obtain ferric phosphate with flaky and blocky composite morphology.

[0058] [Example 4]

[0059] Prepare iron phosphate according to the following method:

[0060] S1. Dissolve 500 g of reduced iron powder in 25% phosphoric acid solution to obtain ferrous dihydrogen phosphate; the raw material is added in a molar ratio of metallic Fe to phosphoric acid of 1:2.5;

[0061] S2, heating the solution to 80°C, adjusting the stirring speed to 100 rpm, adding 110.4 g of 30% hydrogen peroxide, carrying out a first-stage oxidation reaction, and reacting for 10 min to obtain a suspension;

[0062] S3, add maleic anhydride to the suspension at a mass fraction of 1%, stir at 85°C and 100 rpm for 40 min, add 441.6 g of 30% hydrogen peroxide after sufficient mixing, carry out a first-stage oxidation reaction, react for 10 min, adjust the temperature to 95°C and age for 100 min;

[0063] S4, after filtering out the solvent, washing, drying, and calcining at 575°C for 6h to obtain flaky and block-shaped composite iron phosphate.

[0064] [Comparative Example 1]

[0065] Ferric phosphate was prepared in substantially the same manner as in Example 1, except that maleic anhydride was not added in step S3.

[0066] The microscopic morphology of the iron phosphate prepared in this comparative example is as follows Figure 3 As shown, the visible product is only in flake form.

[0067] [Comparative Example 2]

[0068] Ferric phosphate was prepared in a method substantially the same as that of Example 1, except that the maleic anhydride added in step S3 was replaced by phosphoric acid of the same mass.

[0069] The microscopic morphology of the iron phosphate prepared in this comparative example is as follows Figure 4 As shown, the visible product is only in flake form.

[0070]

Application Example 1

[0071] The iron phosphate prepared in Example 1 was used as a raw material and lithium iron phosphate was prepared by sand grinding according to the following method:

[0072] 1000g of iron phosphate was mixed with 501.2g of lithium carbonate, 8g of titanium dioxide and 160g of glucose and placed in a sand mill. The speed of the sand mill was adjusted to 2000 rpm. When the solid D50 reached 550nm, it was spray-dried and calcined at 800°C in a nitrogen atmosphere for 10 hours. The mixture was cooled to room temperature and crushed through a 200-mesh sieve to obtain lithium iron phosphate.

[0073]

Application Example 2

[0074] Lithium iron phosphate was prepared in a method substantially the same as that in Application Example 1, except that the iron phosphate raw material prepared in Example 1 was replaced with the iron phosphate raw material prepared in Comparative Example 1 of the same mass.

[0075]

Application Example 3

[0076] Lithium iron phosphate was prepared in a method substantially the same as that in Application Example 1, except that the iron phosphate raw material prepared in Example 1 was replaced with the iron phosphate raw material prepared in Comparative Example 2 of the same mass.

[0077]

Application example 4

[0078] Lithium iron phosphate was prepared in a method substantially the same as that in Application Example 2, except that the calcination temperature was changed from 800°C to 830°C.

[0079]

Lithium iron phosphate battery performance evaluation

[0080] The lithium iron phosphate is used as raw material to prepare the positive electrode material of lithium battery according to the following method:

[0081] The prepared lithium iron phosphate was used as the positive electrode material, mixed with carbon black and polyvinylidene fluoride (PVDF) cyclohexane solution at room temperature and pressure to form a slurry (according to the effective material mass ratio of positive electrode material: carbon black: PVDF = 85:10:5), and evenly coated on an aluminum foil substrate as the positive electrode of a simulated battery; a lithium sheet was used as the negative electrode of the simulated battery, and the electrolyte was 1 mol LiPF 6Dissolved in 1L of a mixed solvent of EC and DMC (volume ratio 1:1); the separator is a composite film of polypropylene and polyethylene; the positive electrode, negative electrode, electrolyte and separator are assembled into a simulated battery in an argon-protected glove box and the performance of the simulated battery is tested.

[0082] <1C discharge capacity>

[0083] First, charge to 4.2V at 30mA / g, then discharge to 2.5V at 1C current. The released capacity is the 1C discharge capacity.

[0084] <Powder compaction>

[0085] The compaction density of lithium iron phosphate powder was tested under 30kN conditions.

[0086] Table 2. Battery performance test results

[0087] 1C discharge capacity / mAh / g <![CDATA[Powder Compaction Density / g / cm 3 > Application Example 1 145 2.70 Application Example 2 146 2.53 Application Example 3 145 2.52 Application Example 4 137 2.68

[0088] From the comparison between Application Example 2 and Application Example 1, it can be seen that the powder compaction density of lithium iron phosphate prepared by conventional flaky iron phosphate sand grinding is relatively low, and the iron phosphate provided in Example 1 of the present invention has a significantly improved compaction density after being applied to lithium iron phosphate batteries.

[0089] From the comparison between Application Example 3 and Application Example 2, it can be seen that the compaction density and discharge capacity of lithium iron phosphate prepared by sand grinding of flaky iron phosphate provided in Comparative Examples 1 and 2 are similar, with no significant difference, and both cannot reach the high compaction density in Application Example 1 of the present invention.

[0090] From the comparison between Application Example 4 and Application Example 1, it can be seen that when certain means are used to directly increase the compaction density, a certain discharge capacity will generally be lost. After the iron phosphate provided in Example 1 of the present invention is applied to the lithium iron phosphate battery, the powder compaction density is further improved while ensuring a higher discharge capacity, thereby solving the problem that the prior art is difficult to take into account both higher discharge capacity and compaction density.

[0091] In addition, the lithium iron phosphate prepared in Example 1 and Example 4 was observed by scanning electron microscope, and the morphology thereof is shown as follows: Figure 5 , 6 As shown. It can be seen that the lithium iron phosphate particles in Application Example 1 are more uniform in size, without obvious large particles, which is more conducive to the battery capacity; while Application Example 4 uses certain means to directly increase the compaction density of traditional products, with more large particles and uneven particle size, which is presumably the main factor for the loss of discharge capacity.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a morphology-compounded iron phosphate, characterized in that: The following steps are involved: S1, dissolving an iron source in a phosphoric acid solution to obtain a ferrous dihydrogen phosphate solution; S2, heating and stirring, adding a portion of hydrogen peroxide, performing a first-stage oxidation reaction, and obtaining a suspension; S3, adding maleic anhydride to the obtained suspension, mixing and stirring thoroughly, adding the remaining hydrogen peroxide, carrying out a two-stage oxidation reaction, and aging; S4, filtering off the solvent, washing, drying, and then roasting to obtain ferric phosphate.

2. The method for preparing the morphology-compounded iron phosphate according to claim 1, characterized in that: In step S1, the iron source is one or more of reduced iron powder, iron block, iron sheet, ferroferric oxide, and ferrous oxide with a molar purity of metallic Fe greater than 99%; Preferably, the usage ratio of the iron source and the phosphoric acid solution in step S1 is 1:(2-3.5) in terms of the molar ratio of metallic Fe to phosphoric acid; Preferably, the mass concentration of the phosphoric acid solution is 15-40%.

3. The method for preparing the morphology-compounded iron phosphate according to claim 1, characterized in that: In step S2, the heating temperature is 45-95°C, preferably 65-85°C, and the stirring speed is 100-500 rpm.

4. The method for preparing the morphology-compounded iron phosphate according to any one of claims 1 to 3, characterized in that: The total amount of hydrogen peroxide added is 0.5-0.75 times the molar amount of metal Fe in the iron source in terms of molar amount; Preferably, the amount of hydrogen peroxide added in step S2 is 20-80% of its theoretical total amount; Preferably, the mass concentration of the hydrogen peroxide is 20-35%.

5. The method for preparing the morphology-compounded iron phosphate according to any one of claims 1 to 4, characterized in that: In step S2, the first stage oxidation reaction time is 10-50 minutes.

6. The method for preparing the morphology-compounded iron phosphate according to any one of claims 1 to 5, characterized in that: The maleic anhydride is added to the solution obtained in step S2 at a mass fraction of 0.01-10%, preferably 0.5-5%; Preferably, after adding maleic anhydride, the reaction temperature is controlled to be 45-95° C., preferably 65-85° C., the stirring speed is 100-500 rpm, and the mixture is stirred for 20-60 minutes for thorough mixing before adding the remaining hydrogen peroxide.

7. The method for preparing the morphology-compounded iron phosphate according to any one of claims 1 to 6, characterized in that: In step S3, the second stage oxidation reaction time is 10-70 minutes, and after the reaction, the aging reaction is continued at 70-95° C. for 60-120 minutes.

8. The method for preparing the morphology-compounded iron phosphate according to any one of claims 1 to 7, characterized in that: The calcination conditions in step S4 are: calcination at 500-650° C. for 3-6 hours.

9. A morphology-compounded iron phosphate prepared by the method according to any one of claims 1 to 8, characterized in that: It has two composite morphologies, flaky and massive. Preferably, the particle sizes of the flaky and massive microscopic morphologies are comparable.

10. Use of the morphology-compounded iron phosphate prepared by the method according to any one of claims 1 to 8 in the preparation of lithium iron phosphate.

Citation Information

Patent Citations

  • Phosphate positive electrode material and preparation method and application thereof

    CN117303340A

  • Iron phosphate as well as preparation method and application thereof

    CN118324108A

  • Preparation method of composite iron phosphate and lithium iron phosphate positive electrode material

    CN118515253A

  • High-compaction-density lithium iron phosphate positive electrode material and preparation method thereof

    CN118561257A

  • Preparation method of high-capacity and high-compactness composite-structure ferric phosphate for lithium iron phosphate

    CN110436427A

Cited By

  • Method for preparing iron phosphate by circulating oxygen oxidation and application

    CN120136054A

  • Method for preparing battery-grade anhydrous iron phosphate with controllable morphology by iron process

    CN122704866A

  • A three-stage gradient temperature control method for preparing high-purity sheet iron phosphate

    CN122831305A